Serum bone alkaline phosphatase is a useful marker to evaluate lumbar bone mineral density in Japanese postmenopausal osteoporotic women during denosumab treatment - Nakamura Y; Suzuki T; Kato H (Dove Medical Press, 2017)
Yukio Nakamura,1,2 Takako Suzuki,1 Hiroyuki Kato1 1Department of Orthopedic Surgery, Shinshu University School of Medicine, Matsumoto, Japan; 2Department of Orthopedic Surgery, Showa-Inan General Hospital, Komagane, Japan Abstract: A worldwide health concern, osteoporosis (OP), increases the risk of bone fracture and results in morbidity. This study examined whether the representative bone absorption marker serum tartrate-resistant acid phosphatase 5b (TRACP-5b) or bone formation marker bone alkaline phosphatase (BAP) could estimate primary OP status and denosumab efficacy in a real-world setting. We retrospectively enrolled 114 female postmenopausal primary OP patients in Japan. Values and percent changes in TRACP-5b, BAP, lumbar 1–4 bone mineral density (L-BMD), and total hip BMD (H-BMD) were assessed before treatment and at 4, 8, and 12 months of therapy to identify the correlations between the percent changes in bone metabolic markers and BMD. We also established two sets of subgroups based on the upper limits of reference values in Japan for serum: TRACP-5b (<420 mU/dL) and (≥420 mU/dL) and BAP (<14.5 µg/L) and (≥14.5 µg/L). Negative correlations were observed for the percent changes of TRACP-5b and H-BMD at 4 months (r=–0.3476) and 8 months (r=–0.3880), for the percent changes of BAP and H-BMD at 8 months (r=–0.3354), and for the percent changes of BAP and L-BMD at 12 months (r=–0.3186). We observed a significant difference between the subgroups for the percent changes of L-BMD at 8 months (p=0.013) and 12 months (p=0.004) in BAP values. These results suggest that TRACP-5b and BAP had negative correlations with BMD, and that BAP represented a useful serum marker to evaluate L-BMD during denosumab therapy for OP. Keywords: bone mineral density, bone alkaline phosphatase, tartrate-resistant acid phosphatase 5b, denosumab, osteoporosis